Photonic Generation of Neuron-Like Dynamics Using VCSELs Subject to Double Polarized Optical Injection - Xiang, Shuiying; Zhang, Yahui; Guo, Xingxing; Wen, Aijun; Hao, Yue (Journal of lightwave technology, 2018)
We propose to generate excitatory and inhibitory neuron-like dynamics in vertical-cavity surface-emitting lasers (VCSELs) by applying simultaneously the orthogonally-polarized CW optical injection (OPCWOI) and parallelly-polarized pulse optical injection stimulus. Based on the spin flip model, excitatory and inhibitory neuron-like dynamics accompanying with reverse polarization switching is numerically investigated. It is found that, due to the injection locking effect or beating effect between two injected fields, the excitatory phasic and tonic spiking dynamics can be obtained in the originally dominated polarization mode. Moreover, the unwanted relaxation oscillation followed by the excitatory spiking dynamics at the end of the stimulus pulse, which is present in previous reported photonic neuron based on the VCSELs subject to a single orthogonally-polarized optical pulse injection, can be completely suppressed. In addition, the inhibition of tonic spiking dynamics can also be achieved, and the transition from tonic spiking dynamics to phasic bursting dynamics can be obtained, when the two injected fields have the same frequency. These results are interesting and valuable for the ultrafast photonic neuromorphic systems and neuron-inspired photonic information processing.